Tata kelola pendidikan seni berbasis komunitas dan kontribusinya terhadap pembangunan budaya dan pendidikan berkelanjutan" - Lesa Paranti; Restu Lanjari; Rahina Nugrahani; Phakamas Jirajarupat (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2025)
This study examines how community-based arts education governance at Sanggar Juju in Semarang contributes to the achievement of Sustainable Development Goals (SDGs) 4 (Quality Education) and 11 (Sustainable Cities and Communities) through cultural preservation. Utilizing qualitative methods, data were collected via observations, in-depth interviews, and documentation. Data analysis included reduction, presentation, and verification, with triangulation used to ensure validity. The findings reveal that the success of Sanggar Juju in managing its programs and growing its membership to 125 students over six years is underpinned by governance practices such as a policy framework, organizational values, participatory principles, and accountability systems. The studio promotes SDG 4 by offering culturally relevant and inclusive learning opportunities in traditional dance and supports SDG 11 by preserving intangible cultural heritage, strengthening social cohesion, and boosting community-based tourism in Kandri Village. Despite these successes, the organization still employs a centralized leadership model, which limits transparency and participation, posing risks to its sustainability and external funding opportunities. The study recommends adopting a collaborative governance model to improve accountability mechanisms, ensuring long-term organizational resilience and enhancing its contribution to the SDGs.